1978
DOI: 10.1121/1.381772
|View full text |Cite
|
Sign up to set email alerts
|

Cross-language study of speech-pattern learning

Abstract: In order to investigate the nature of some processes in speech acquisition, synthetic speechlike stimuli were played to groups of English and French children between two and fourteen years of age. The acoustic parameters varied were voice onset time and first-formant transition. Three stages were observed in the development of children’s labeling behavior. These were called scattered labeling, progressive labeling, and categorical labeling, respectively. Individual response patterns were examined. The first st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
39
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…At the nonspeech level, this is in line with (1) physiological animal studies showing that neural coding for temporal aspects of the stimulus reaches maturity later than neural coding for frequency selectivity (Eggermont, 1996), and with (2) behavioral auditory studies in humans providing evidence for a more prolonged development of the sensitivity for temporal than for nontemporal auditory cues (Hartley, Wright, Hogan, & Moore, 2000), even after accounting for the effect of procedure-related skills (Dawes & Bishop, 2008). At the speech level, it coincides with behavioral speech perception studies demonstrating that the identification of stop consonants is not yet mature by the age of 11 (Hazan & Barrett, 2000;Johnson, 2000;Krause, 1982;Simon & Fourcin, 1978;Medina, Hoonhorst, Bogliotti, & Serniclaes, 2010), whereas the identification of vowels does only slightly, though not significantly, improves towards adolescence (Pursell, Swanson, Hedrick, & Nabelek, 2002;Ohde, Haley, & McMahon, 1996;Johnson, 2000, but see Walley and Flege, 1999). Further elaboration on this topic is needed, but the indication that perception of sounds with temporal versus nontemporal cues follows different maturational trajectories in both normal and dyslexic readers, may have practical implications with regard to auditory temporal training programs.…”
Section: Discussionsupporting
confidence: 49%
“…At the nonspeech level, this is in line with (1) physiological animal studies showing that neural coding for temporal aspects of the stimulus reaches maturity later than neural coding for frequency selectivity (Eggermont, 1996), and with (2) behavioral auditory studies in humans providing evidence for a more prolonged development of the sensitivity for temporal than for nontemporal auditory cues (Hartley, Wright, Hogan, & Moore, 2000), even after accounting for the effect of procedure-related skills (Dawes & Bishop, 2008). At the speech level, it coincides with behavioral speech perception studies demonstrating that the identification of stop consonants is not yet mature by the age of 11 (Hazan & Barrett, 2000;Johnson, 2000;Krause, 1982;Simon & Fourcin, 1978;Medina, Hoonhorst, Bogliotti, & Serniclaes, 2010), whereas the identification of vowels does only slightly, though not significantly, improves towards adolescence (Pursell, Swanson, Hedrick, & Nabelek, 2002;Ohde, Haley, & McMahon, 1996;Johnson, 2000, but see Walley and Flege, 1999). Further elaboration on this topic is needed, but the indication that perception of sounds with temporal versus nontemporal cues follows different maturational trajectories in both normal and dyslexic readers, may have practical implications with regard to auditory temporal training programs.…”
Section: Discussionsupporting
confidence: 49%
“…weighting strategies for speech are not always the same as those of adults (Greenlee, 1980;Krause, 1982;Morrongiello, Robson, Best, & Clifton, 1984;Nittrouer, 1992Nittrouer, , 1996Nittrouer, Crowther, & Miller, 1998;Nittrouer & Miller, 1997a, 1997bNittrouer & Studdert-Kennedy, 1987;Parnell & Amerman, 1978;Simon & Fourcin, 1978;Wardrip-Fruin & Peach, 1984). Of particular relevance to the present study, earlier work has repeatedly found differences between children and adults in labeling decisions of syllable-initial Iflor lsi (Nittrouer, 1992(Nittrouer, , 1996Nittrouer & Miller, 1997b;Nittrouer & Studdert-Kennedy, 1987).…”
mentioning
confidence: 57%
“…Therefore, the present research assessed categorical perception of a differ in either the phonological presence/absence or the phonetic realization of the target contrasts tested. Languagespecific group differences in categorical perception have been found for stop consonant voicing distinctions (voice onset time; e.g., Abramson & Lisker, 1970;Keating, Miko , & Ganong, 1981;Simon & Fourcin, 1978;Williams, 1977), place of articulation distinctions (Werker & Lalonde, 1988), and approximant place distinctions (Best & Strange, 1992;Hallé et al, 1999;MacKain, Best, & Strange, 1981;Miyawaki et al, 1975). Importantly, language-specific perceptual effects have also been found for phonological distinctions that are perceived much less categorically: vowels (Stevens et al, 1969) and lexical tone contrasts.…”
mentioning
confidence: 87%